Social actions developed with families of students from the public school system in the Caparaó region - Aparecida da Silva Martins, Camila; Lorenzoni Marotto, Gracieli; Binda Silva Costa, Ariany; Guimarães, Damaris; Falqueto Salvador, Fernanda; Costa de Sousa, Robson; Crevelari Lachini , Carina; Silva de Mattos, Dayana (Guará Journal, 2024)
Brazil was one of the countries hardest hit by the COVID-19 pandemic, and as a result, a series of biosafety measures were implemented to reduce exposure to the novel coronavirus. Among these measures, social distancing, which led to school closures and the interruption of access to meals, stands out, directly affecting children and adolescents from low-income families. Therefore, this work aims to present the results of outreach initiatives developed during the COVID-19 pandemic, carried out in five municipalities in the Caparaó region: Alegre, Guaçuí, Ibatiba, Ibitirama, and São José do Calçado. A questionnaire was administered to obtain information about the profile of the families assisted by the project, and subsequently, a socio-educational awareness campaign was carried out, supported by a booklet and infographic prepared by the project partners before the delivery of basic food baskets and COVID-19 prevention kits to the families. These social initiatives helped a total of 72 families and approximately 347 individuals. The extension project had a positive social impact and enabled a network of solidarity between the university and the community, which contributed to the expansion of knowledge and the transmission of information.